Design a Recommendation System for Ngawi Regency Tourist Attractions Using the Simple Additive Weighting Method - Pramudea Yohano Firmansyah; Muhammad Zakariyah (SEAN Institute, 2023)
Ngawi Regency is an area in East Java Province which is directly adjacent to Central Java Province. The area of Ngawi Regency has an area of 1,298.58 km2. With this area, of course, Ngawi Regency has various types of diverse tourist attractions, such as natural tourism, historical tourism, agro-tourism, water tourism, religious tourism, and many more. So do not be surprised if there are people and even I find it difficult to determine which tourist attractions to visit. This study aims to help determine recommendations for tourist attractions using the calculation of the Simple Additive Weighting (SAW) method. So, tourist attractions will be ranked based on the preference value that has been calculated using the Simple Additive Weighting (SAW) method. The results showed that the system can rank the data of a tourist spot with a set of weighted criteria defined by users and then the tourist attractions are sorted from high to low preference values and display information related to the object so that users can be helped when they want to determine the tourist attractions to be visited and get detailed information related to the tourist attractions.